THE TIMING OF PARTURITION AND SEX RATIO IN YAKS UNDER FARM CONDITION - DEORI, S; BAM, JOKEN (The Indian Journal of Animal Reproduction, 2023)
The yak is a multipurpose species and is believed to be indispensable for the highlanders of central Asian countries. Study was designed to investigate the hourly distribution of time of parturition and sex ratio in yak managed underfarm conditions in eastern Himalayas. 268 calving data were recorded from 2001 to 2010 of yaks that ranged from 3 to 8 years of age and managed under uniform conditions. The maximum calving occurred between 00.00- 06.00 hours and least calving were recorded between 18.00- 24.00 hours. Overall, in comparison to day time (06.00-18.00 hours) more calving were seen during night time (18.00- 06.00 hours). When calving times were examined with respect of sex of the calf a similar pattern of the hourly distribution were found in both sexes. The overall secondary sex ratio was found to be 51.1 % male and 48.9% female. Maximum calving occurred between May to October in yaks. During these period highest percentage of female birth was seen during the August and male birth in the month of May.